GE_GERICHTE C/4705/2013 vom 26. Juni 2015 - GE Cour de justice (2015)
HONORAIRES; RÉMUNÉRATION SELON LES PRESTATIONS; PREUVE; RENONCIATION(SENS GÉNÉRAL); MAXIME DES DÉBATS | CPC.55.1; CPC.152.1; CO.394.3